An investigation of the effects of the choice of stacking velocities on residual statics for hardrock reflection seismic processing - Malehmir, A.; Juhlin, Christopher (2010)
Crystalline rocks are typically deformed, folded and altered and contain interfaces that have varying dips. These interfaces are often short in length and sometimes can be represented as diffractors. Imaging of reflections from these interfaces, which are often of low acoustic impedance contrast, poses a challenge in reflection seismic data processing. An important step in the imaging process is the calculation of residual statics. In this study we investigate the effects of the choice of stacking velocities on the estimation of surface-consistent residual statics in the crystalline environment on a synthetic data set and two real data examples, one 2D data set and a 3D one. On the synthetic data set, residual statics were estimated using three different approaches. In the first approach (normal move out or NMO approach), residual statics were estimated using an NMO velocity function that focuses on steeply dipping reflections and uses velocities ranging from 5000 to 9000. m/s. In the second approach (dip move out or DMO approach), residual statics were estimated using the true media velocity or using an updated velocity function after the implementation of DMO corrections. For the third approach, single reflections were focused on for the residual statics estimation. Analysis of the resulting stacked sections, as well as the estimated residual statics, shows that when short steeply dipping reflections are present, the DMO approach allows better imaging of diffractions and gently dipping reflections. High-stacking velocities in the NMO approach produce more coherent noise, which negatively influences the estimation of residual statics. The best estimation of residual statics can be obtained if the calculation focuses in a narrow window along sub-horizontal or gently dipping reflections. Such reflections will not always be present in real data and the synthetic test shows that focusing on steeply dipping reflections within a narrow window, in the absence of horizontal or gently dipping reflections, provides superior results compared with a wide search window. Application of these approaches on real seismic data acquired over crystalline rocks demonstrates that an improper estimation of surface-consistent residual static corrections can result in the loss of short gently dipping reflections and diffractions that may be an indication of mineral deposits. © 2010 Elsevier B.V.